Mandi Safar Tradition at Tasik Nambus Kepulauan Meranti Riau Society (Viewed from the Perspective of Hadits) - Miftahul Fikria; Muh. Fathoni Hasyim (UIN Sumatera Utara Medan, 2023)
This article discussed about Mandi Safar Tradition at Tasik Nambus, the society of kepulauan Meranti Regency, Riau (Viewed from the Perspective of Hadits). The purpose of this study is to review the values contained in mandi safar according to hadits perspective. So that Islamic values are found in it. Because there are still many people who think that the traditions that develop in society are against the Shari'a, including the tradition of taking a mandi safarin Kepulauan meranti Regency. This study used a qualitative method, using two methods, namely by interviewing community leaders and exploring the literature related to research. As for the results of the study it was found that the Mandi Safar tradition of the society of the Kepulauan Meranti Regency is a hereditary tradition. This tradition started since the discovery of Tasik Nambus, the main character is Muhammad Sholeh. The Mandi Safar procession has two stages, namely preparation and implementation. The preparatory stage consists of soaking the wafak and preparing food, while the procession stage begins with praying together, eating together and bathing in Tasik Nambus, and this tradition is still running today. Based on the procession that was carried out, it was found that the values contained in the Mandi Safar tradition at Tasik Nambus, namely surrendering to God, giving charity and staying in touch. These three values when viewed from the perspective of hadith are recommended, the hadith also doesn’t conflict with Al-Qur'an and common sense.